EVOLUTION OF THE CRAB NEBULA RADIO EMISSION - Vinyajkin, E. N. (Одеські астрономічні публікації, 2017)
In 1977-1992 the flux density of the Crab Nebula in respect to Orion Nebula was measured at the frequency of 927 MHz with the same 10-m radio telescope. According to these measurements a mean rate of the Crab Nebula radio emission decline, (0.44 ±0.16)% per year, was determined. This value is considerably more than the value (0.18 ± 0.01)% per year obtained for the previous fifteen years 1962-1977 (Vinyajkin E.N.. Razin V.A.: 1979, Austral J. of Physics, 32, 93). It is possible that in addition to the steady secular decline of the Crab Nebula radio emission flux there are the flux fluctuations responsible for the variability of the mean radio emission flux decline rate determined with the use of ≈ 15—year periods observational data. The most probable cause of these fluctuations is a discreteness of the Crab Nebula radio structure.